Criação, Experiência E Compartilhamentos – O Ser E Estar Artista Professor. (Revista Apotheke, 2019)
This essay, inserted in the debate around the theme "Artist Professor - be and being", brings together several personal reflections on the theme, also considering the experience of this researcher as a starting point. At the core of this question, the reflection to be developed should follow the be and being of this artist/professor, asking what it means to be one and the other, or just being full-time, am I or I am being an artist/ professor?
Keywords: artist-teacher; contemporany art; creation; experience; teaching